Efficacy of Curcumin on Treating Cancer Anorexia-Cachexia Syndrome in Locally or Advanced Head and Neck Cancer: A Double-Blind, Placebo-Controlled Randomised Phase IIa Trial (CurChexia) - Tawasapon Thambamroong; Kasan Seetalarom; Siriwimon Saichaemchan; Yanisa Pumsutas; Naiyarat Prasongsook (Journal of Nutrition and Metabolism)
Background. Cancer anorexia-cachexia syndrome (CAS) is a significant comorbidity among all patients with cancer, increasing the mortality rate. Almost all patients with head and neck cancer experience this syndrome. CAS causes increased energy expenditure by increasing systemic inflammation and decreasing energy consumption due to anorexia. It leads to skeleton muscle breakdown and reduces the quality of life. Nutritional interventions and primary cancer treatment are the mainstays to manage this situation. However, a vicious cycle causes CAS to persist, especially in head and neck cancer, where tumour location and its treatment interfere with nutritional interventions. Curcumin shows anti-inflammatory effects, including modulated CAS in animal and in vitro studies. Objective. The study aimed to determine the effect of curcumin to treat cancer anorexia-cachexia syndrome among current patients with locally advanced or advanced head and neck cancer. Methods. This constitutes a randomised, double-blind, placebo-controlled phase IIa study. Twenty patients with CAS in locally advanced or advanced head and neck cancer adequately nourished via a feeding tube were enrolled and randomised in a 1 : 1 ratio to receive oral curcumin (at a dose of 4000 mg daily) (n = 10) or placebo (n = 10) for 8 weeks. The primary endpoint was body composition (muscle mass, body fat mass, and basal metabolic rate). The secondary endpoints were handgrip muscle strength, body mass index, absolute lymphocyte count, and safety and toxicity. Result. There was a statistically significant benefit from curcumin on improving muscle mass compared with placebo (2.16% [95% confidence interval; CI, −0.75 to 5.07] vs. −3.82% [95% CI, −8.2 to 0.57]; P=0.019). The other parameters of body composition were not significant but tended to favour curcumin benefit. The body fat mass (−0.51 [95% CI, −21.89 to 20.86] vs. −8.97% [95% CI, −19.43 to 1.49]; P=0.432) and percentage of mean change in the basal metabolic rate were noted (BMR) (0.54% [95% CI, −1.6 to 2.67] vs. −1.61% [95% CI, −4.05 to 0.84]; P=0.153). Notably, patients treated with curcumin exhibited less reduction in handgrip muscle strength and absolute lymphocyte count but was not significant. Similarly, most adverse events were grade 1 in both groups. Conclusion. The curcumin add-on resulted in a significant increase in muscle mass than standard nutritional support. Furthermore, it may improve and delay a decrease in the other body composition parameters, handgrip strength, and absolute lymphocyte count. Curcumin was safe and well tolerated. This constitutes an unmet need for clinical trials. This trial is registered with NCT04208334.